Sensitivity of PCR in conjunctival swab samples for the diagnosis of canine visceral leishmaniasis: a systematic review and meta-analysis - Mariana Fagundes Bento; Gabriela Scarpin de Souza; Bruno Serpa Vieira; Ângela Adamski da Silva; Felipe da Silva Krawczak; Veridiana Maria Brianezi Dignani de Moura (Revista Brasileira de Parasitologia Veterinária, 2023)
Abstract To compare the sensitivity of conjunctival swab (CS) and conventional samples (blood, spleen, liver, lymphoid and cutaneous tissue) in the diagnosis of canine visceral leishmaniasis (CVL) by polymerase chain reaction (PCR), a systematic review and meta-analysis was carried out using PubMed, Science Direct, Scopus, Web of Science, VHL/BVS (Virtual Health Library), CAPES, and Scielo databases. Articles published from 2002 to 2022 were considered and the review was updated in Jul 2023. From the total of 371 identified studies, 8 met all the eligibility criteria and were included in this review. Data from 658 CVL-positive dogs and 2541 PCR results were considered. Using a random effect model, data on the sensitivity of the test was compared between intervention (CS samples) and comparison (all the other samples) groups. Overall, the use of CS in the PCR diagnosis of CVL produced 12% higher sensitivity (p=0.013) in the test than all the other samples in combination. The animals' clinical condition did not influence (p>0.142) this overall result. However, when CS was individually compared to each of the conventional samples, the consistent result was observed (p=0.012) only in the CS versus bone marrow comparison. Given their rapid acquisition, minimal invasiveness, and lower cost relative to conventional samples, CS samples present a promising alternative for the molecular diagnosis of CVL.